Contraception, female cycle disorders and injuries in Swiss female elite athletes—a cross sectional study - Baumgartner, Sabrina; Bitterlich, Norman; Geboltsberger, Sarah; Neuenschwander, Maja; Matter, Sibylle; Stute, Petra (Frontiers in Physiology, 2023)
Aim: The national Olympic committee of Switzerland has conducted an online survey among female elite athletes with a focus on cycle disorders, contraception, and injuries in 2021. Methods: A total of 1092 female elite athletes from 107 different sports were asked to answer the questionnaire. A descriptive analysis was carried out to determine location parameters and create frequency tables. Results: The questionnaire was completed by 408 athletes (37.4 %) from 92 different sports. 43.4 % participated in a lean sport. 57.1 % reported no injuries, 32.6 % one injury, and 10.2 % two or more injuries per year. A considerable proportion reported being affected by primary amenorrhoea (10.8 %). Primary amenorrhoea occurred significantly more often in female athletes with a BMI lower than 21.7 kg/m2 (15.2 %) than in athletes with a BMI above 21.7 kg/m2 (7.4 %, p=0.021). Considering contraception, 25.8 % of female athletes were currently using an oral contraceptive pill. The proportion of female athletes not using contraception at all or using non-hormonal contraceptive methods was high at 54.4 %. In lean sports, significantly more athletes used no or non-hormonal contraceptives (p<0.05). Conclusion: Among top Swiss female athletes, a considerable proportion used non-hormonal or no contraceptives. This trend was more evident in lean sports. Delayed menarche and cycle irregularities were common among female athletes, especially among athletes with high training volumes as well as a BMI below 21.7 kg/m2. This orienting survey underlines the importance of specialized gynecological care for elite female athletes.